An Almost General Code in R to Find Optimal Designs (MATEMATIKA, 2013)
Optimal designs play an important role in many applied areas such as medical and industrial research. Depending the model, finding the optimal design needs an optimization process based on the Fisher information matrix. Using a nice technique in R (a very popular statistical software), an almost general code can be used for many various cases of optimization processes. Keywords: Experimental designs; Locally D-optimal designs; Fisher information matrix; R. 2010 Mathematics Subject Classiffication: 62K05